Neuroinflammation and Not Tauopathy Is a Predominant Pathological Signature of Nodding Syndrome. Issue 11 (6th September 2019) - Hotterbeekx, An; Lammens, Martin; Idro, Richard; Akun, Pamela R; Lukande, Robert; Akena, Geoffrey; Nath, Avindra; Taylor, Joneé; Olwa, Francis; Kumar-Singh, Samir; Colebunders, Robert
Abstract: Nodding syndrome (NS) is an epileptic disorder occurring in children in African onchocerciasis endemic regions. Here, we describe the pathological changes in 9 individuals from northern Uganda who died with NS (n = 5) or other forms of onchocerciasis-associated epilepsy (OAE) (n = 4). Postmortem examinations were performed and clinical information was obtained. Formalin-fixed brain samples were stained by hematoxylin and eosin and immunohistochemistry was used to stain astrocytes (GFAP), macrophages (CD68), ubiquitin, α-synuclein, p62, TDP-43, amyloid β, and tau (AT8). The cerebellum showed atrophy and loss of Purkinje cells with hyperplasia of the Bergmann glia. Gliosis and features of past ventriculitis and/or meningitis were observed in all but 1 participant. CD68-positive macrophage clusters were observed in all cases in various degrees. Immunohistochemistry for amyloid β, α-synuclein, or TDP-43 was negative. Mild to sparse AT8-positive neurofibrillary tangle-like structures and threads were observed in 4/5 NS and 2/4 OAE cases, preferentially in the frontal and parietal cortex, thalamic- and hypothalamic regions, mesencephalon and corpus callosum. Persons who died with NS and other forms of OAE presented similar pathological changes but no generalized tauopathy, suggesting that NS and other forms of OAE are different clinical presentations of a same disease with a common etiology.